Peningkatan Pengetahuan Perilaku Hidup Bersih dan Sehat Rumah Tangga - Wulan Angraini; Henni Febriawati; Muhammad Amin (Jurnal Kesmas Asclepius, 2022)
This study aims to determine the increase in knowledge of household clean and healthy behavior in an effort to create a healthy family at the UPTD Puskesmas Kuala Lemruban, Bengkulu City. This research method is a descriptive study with a cross sectional design. The results of the research on health education at the pre-test were 57.69 and the mean post-test was 74.62 with a p-value of 0.000. In conclusion, there is a significant effect of health education on Clean and Healthy Life Behavior in UPTD Puskesmas Kuala Lemruban, Bengkulu City. Keywords: Improvement, Counseling, Clean and Healthy Life Behavior